Dynamic collision detection algorithm and application - Zhao Lala; Zhao Yuemin; Liu Chusheng; Dong Hailin (2011 International Conference on Consumer Electronics, Communications and Networks, 2011)
Aiming at the problems of penetration and missing detection between particles with high speed in virtual system, a dynamic detection algorithm is presented which efficiency is advanced by the combination of multilevel detection and detection space division method in this paper. The algorithm has been applied in virtual sieving experiment system of discrete material and the results meet a good agreement with industrial experiment. It shows that dynamic collision detection algorithm can avoid the problems of penetration and missing detection between particles with high moving velocity and improve the precision of virtual sieving test. The algorithm is simple and with high efficiency which is suitable for simulation of complex virtual scene with large number of dynamic particles.